(untitled) (Revista Escenarios Sociojurídicos, 2025)
The objective of this article was to analyze the criminal profile of homicidal women against their spouse or permanent partner in the department of Atlántico. It also sought to identify the applicability of self-defense as a cause for the absence of criminal responsibility in cases of women who kill their spouse. or permanent partner, also sought to interpret the criminal behavior of homicidal women from criminology. In this way, the conduct of the criminal subjects was interpreted, taking into account the modus operandi, the signature and seal, the crime scene and the regulatory component that allows recognizing the existence of fundamental procedural guarantees of national and international rights that shed light to international conventions, the Political Constitution of Colombia, the Colombian Penal Code and current Decree-Laws. On the other hand, its investigative applicability was the development of a type of qualitative approach and design with a historical-hermeneutic paradigm, whose technique and instrument for collecting information was documentary review and text analysis, on the population of women who have been seen in the full commission of the crime of homicide within the family as a consequence of previous actions of domestic violence, in the department of Atlántico, Colombia. Finally, as research results, we sought to socialize the analysis of the criminal profile of the aforementioned women and interpret this phenomenon as a social damage, which as a conclusion gives way to domestic violence and homicide as a socio-legal problem.